THE EFFECTS OF READING INTEREST AND VOCABULARY MASTERY TOWARDS WRITING SKILL IN DESCRIPTIVE TEXT - Verianus da Silva Wadu; Supeno Supeno (INFERENCE: Journal of English Language Teaching, 2021)
This research aims to get empirical data and analyze the effects of reading interest and vocabulary mastery on students’ writing skills at State Vocational High Schools in Tangerang City, Banten. This research was designed and calculated using quantitative calculation. The research findings indicated: (1) There are significant effects of reading interest and vocabulary mastery towards students’ writing skills. It is proved by Sig is 0,000 < 0,05 and the value of F0 is 47,110. (2) There is a significant effect of reading interest on students’ writing skills. It is proved by the Sig is 0,044 < 0,05 and the value To is 2,078. (3) There is no significant effect of vocabulary mastery on students writing skills. The Sig proves it is 0,142 >0,05, and the value of To is 1,603. Due to the result, it can be inferred that there was a significant effect of students’ reading interest and vocabulary mastery towards students’ writing skills. The students' higher writing skill is influenced by the vast amount of vocabulary mastery and other influential factors such as a high reading interest.